Financing for Retirement and the 2007-2009 Unwinding of the Financial Sector - Piffaretti, Nadia F. (2012)
This paper explores the macroeconomic implications of financing for retirement in advanced economies. It offers an additional theoretical explanation of the possible long-term drivers of the 2007-2009 financial crisis. It develops a simple integrated macro-financial model of monetary production, and suggests that the increasingly systemically important retirement institutions present incentives not aligned with the macroeconomic needs of financing for retirement. It thus identifies demographic change and retirement finance as one of the underlying causes of build-up of intrinsic fragility in the financial sector.